Resonant leadership practices of nurse managers in the hospital setting - Reynolds, Petrinella Onetia Fiana (2021)
Introduction: Nursing managers play a pivitol role in hospital\'s management; and with it comes a great responsibility, from assisting with patient care and saftey to promoting quality work life of the nurses and also supporting the changes that arises with these responsibilities. In doing so, it is required of them to be a source of empowerment to the nurses so they are able to perform their duties using the best practices necessary. Additionally, nurse managers are required to ensure staff commitment by creating and maintaing a work environment that is promotes quality patient care. Objective: The aim of this study is to analyze resonant leadership style among the nurse managers at the Georgetown Public Hospital from the perspective of nurse managers and registered nurses. Method: this was a cross-sectional survey, where the data was obtained from managers and registered nurses at Georgetown public hospital. Hard copy questionnaires were distributed to randomly selected nurses and nurse managers. One hundred seventy-one (171) were completed, representing a response rate of 62%. The resonant leadership questionnaire was used for both nurses and nurse managers. The SPSS program version 23 was employed. For the quantitative variables, the following descriptive measures were calculated: mean, standard deviation, median and minimum and maximum values. To calculate the association between sociodemographic and work variables and resonant leadership, the ANOVA test was used. A significance level of 5% was employed for deciding the outcome of each statistical test conducted. Results: In this study, nurses perceive their managers to have moderate levels of resonant leadership practice in the setting. The maximum rating was a perfect 50. The arithmetic mean rating is 33.1 and this almost ideally coincides with the median, which is 34.0. The standard deviation is 9.5 and this, together with the mean suggest there are no extreme values. The results of this study show that resonant leadership was practiced at a moderate level in the hospital\'s acute care setting. This study demonstrate that resonant leadership does not depend on the sub categories of the demographic variables except for the age when the managers evaluated themseves. Ressonant leadership is not associated with the work variables. Conclusion: The result findings suggest that resonant leadership is sometimes encourage to be practiced or that there is a lack of organizational support for such practice. This gives a negative implication that the nursing fraternity of the hospital are somewhat unaware of this leadership style or that the continuous education curriculum for nurses at this hospital may not have resonant leadership and emotional intelligence on their agenda.